A randomized, open‐label clinical trial of tasisulam sodium versus paclitaxel as second‐line treatment in patients with metastatic melanoma. Issue 13 (26th March 2014) - Hamid, Omid; Ilaria, Robert; Garbe, Claus; Wolter, Pascal; Maio, Michele; Hutson, Thomas E.; Arance, Ana; Lorigan, Paul; Lee, Jeeyun; Hauschild, Axel; Mohr, Peter; Hahka‐Kemppinen, Marjo; et al.
Abstract : BACKGROUND: Tasisulam sodium (hereafter referred to as tasisulam) is a novel, highly albumin‐bound agent that demonstrated activity in a phase 2 melanoma study. METHODS: In this open‐label phase 3 study, patients with AJCC stage IV melanoma received tasisulam (targeting an albumin‐corrected exposure of 1200‐6400 h (hour).μg/mL on day 1) or paclitaxel (80 mg/m 2 on days 1, 8, and 15) every 28 days as second‐line treatment. RESULTS: The study was placed on clinical hold after randomization of 336 patients when a safety review indicated an imbalance of possibly drug‐related deaths in the tasisulam arm. Efficacy results for tasisulam versus paclitaxel revealed a response rate of 3.0% versus 4.8%, a median progression‐free survival of 1.94 months versus 2.14 months ( P  = .048), and a median overall survival of 6.77 months versus 9.36 months ( P  = .121). The most common drug‐related grade ≥3 laboratory toxicities (graded according to Common Terminology for Adverse Events [version 3.0]) were thrombocytopenia (18.9%) for patients treated with tasisulam and neutropenia/leukopenia (8.7%) among those receiving paclitaxel. There were 13 possibly related deaths reported to occur on the study, with the majority occurring during cycle 2 in the setting of grade 4 myelosuppression, all in the tasisulam arm. Investigation of the unexpectedly high rate of hematologic toxicity revealed a subset of patients with low tasisulam clearance, leading to drug accumulation and high albumin‐corrected exposure in cycle 2. CONCLUSIONS: Although the study was stopped early because of safety issues in the tasisulam arm, tasisulam was considered unlikely to be superior to paclitaxel, and paclitaxel activity in the second‐line treatment of melanoma was much lower than expected. The toxicity imbalance was attributed to an unexpectedly low tasisulam clearance in a subset of patients, underscoring the importance of pharmacokinetic monitoring of compounds with complex dosing, even in late‐phase studies. Cancer 2014;120:2016–2024 . © 2014 American Cancer Society . Abstract : The current phase 3 melanoma trial demonstrated greater hematologic toxicity in the group of patients treated with tasisulam compared with those receiving paclitaxel, which was attributed to low tasisulam clearance in a subset of patients. These results underscore the importance of pharmacokinetic monitoring of compounds with complex dosing, even in late‐phase studies.